Analysis of Indonesia Marine Fisheries with Economic Growth, Population and Effort Effectiveness (European Journal of Formal Sciences and Engineering, 2022)
Fisheries, as part of the human food chain, have an environment that affects fisheries resources. The view of slowing the number of fish catches in the sea due to factors that drive such as economic growth, population and effort effectiveness will decrease the power of fish in the sea. This study carried out the circumstance of fisheries in sea Indonesia and analyzed empirically the relationship between economic factors, population, and effort effectiveness on the catch volume. We apply the random effect (RE) estimator method which is reviewed for 33 provinces for the period 2000-2015. We use catch as a proxy for marine ecosystems. Our results confirmed that the growth of fish catchment in the sea Indonesia experienced a positive trend and the relationship between economic factors, population and effort effectiveness positive and significant on the volume of catch thus we conclude that catch fisheries in Indonesia is sustainable
Keywords: Indonesia marine catch, Fish stock, Fisheries